Embryonic heat conditioning increases lipolytic gene expression in broiler chicks at day 4 post-hatch - Sulaiman, Usman; Vaughan, Reagan S.; Siegel, Paul; Liu, Dongmin; Gilbert, Elizabeth Ruth; Cline, Mark Andrew (Frontiers in Physiology, 2024)
Exposure to elevated temperatures during incubation is known to induce epigenetic changes that are associated with immunological and stress-response differences at a later age. Reports on its effects on the adipose tissue are still scarce. In this experiment, we investigated the effect of embryonic heat conditioning (EHC) on growth, adipose tissue mRNA and global DNA methylation in broiler chicks at day 4 post-hatch. Fertile eggs were divided into two groups: control and EHC. Eggs in the control group were incubated at 37.8℃ and 80% relative humidity from day 0 to day 18.5 (E0 to E18.5). The EHC eggs were subjected to an intermittent increase in temperature to 39.5℃ and 80% relative humidity from E7 to E16 for 12 hours (07:30-19:30) per day. On day 4 post-hatch, control and EHC chicks were subjected to 36℃ using three time points: 0 (no heat challenge serving as the control), and 2 and 12 hours relative to start of the heat challenge. Fifteen chicks were sampled from each group for every timepoint. Body weight was recorded before euthanasia and subcutaneous adipose tissue was collected. Body weights were similar in control and EHC groups. Diacylglycerol O-acyltransferase 2 (DGAT2) mRNA was lower in the EHC group at time 0 relative to control. Hormone-sensitive lipase (HSL) mRNA was greater in the EHC than control group at the 0 hour timepoint. Heat challenge affected adipose tissue DNA methylation, with methylation highest at 12 hours into the heat challenge. These findings highlight the dynamic molecular responses of chicks to heat stress during early posthatch development and suggest that EHC may affect heat stress responses and adipose tissue development through mechanisms involving lipid remodeling and DNA methylation.